1992
DOI: 10.1161/01.cir.86.4.1116
|View full text |Cite
|
Sign up to set email alerts
|

Role of alpha 2-adrenoceptors in normal and atherosclerotic human coronary circulation.

Abstract: The selective in vivo stimulation of alpha 2-adrenoceptors produces a reduction in coronary blood flow and diameter in humans with angiographically normal coronary arteries. alpha 2-Adrenergic blockade does not change coronary blood flow in subjects with angiographically normal coronary arteries (suggesting no resting alpha 2-adrenergic vasoconstrictor tone), whereas in patients with coronary artery stenosis, regional coronary blood flow decreases after alpha 2-receptor blockade. Finally, our data also suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 31 publications
0
32
0
2
Order By: Relevance
“…23 In patients with coronary artery disease, intracoronary infusion of the selective ␣ 2 -antagonist yohimbine with concomitant ␤-blockade increased coronary sinus norepinephrine levels and reduced both epicardial diameter and coronary blood flow velocity, possibly because of enhanced ␣ 1 -adrenoceptor activation. 31 An increase in coronary vascular resistance index in response to intravenous norepinephrine was found in patients with coronary artery disease. 42 Baumgart et al, 32 using intracoronary infusion of the selective ␣ 1 -agonist methoxamine at increasing doses in patients with coronary artery disease, reported constriction of both epicardial and resistive coronary vessels.…”
Section: Enhanced ␣-Adrenergic Vasoconstriction In Patients With Estamentioning
confidence: 99%
See 1 more Smart Citation
“…23 In patients with coronary artery disease, intracoronary infusion of the selective ␣ 2 -antagonist yohimbine with concomitant ␤-blockade increased coronary sinus norepinephrine levels and reduced both epicardial diameter and coronary blood flow velocity, possibly because of enhanced ␣ 1 -adrenoceptor activation. 31 An increase in coronary vascular resistance index in response to intravenous norepinephrine was found in patients with coronary artery disease. 42 Baumgart et al, 32 using intracoronary infusion of the selective ␣ 1 -agonist methoxamine at increasing doses in patients with coronary artery disease, reported constriction of both epicardial and resistive coronary vessels.…”
Section: Enhanced ␣-Adrenergic Vasoconstriction In Patients With Estamentioning
confidence: 99%
“…29 Part of the increase in coronary reserve with doxazosin could be attributed to increased circulating catecholamines in response to dipyridamole. 30 Using the selective ␣ 2 -antagonist yohimbine in the presence of ␤-blockade, Indolfi et al 31 found no changes in epicardial diameter and coronary blood flow velocity in patients with atypical chest pain but angiographically normal coronary arteries. Baumgart et al, 32 using intracoronary infusion of the selective ␣ 1 -agonist methoxamine at increasing doses, observed no vasoconstriction of normal epicardial coronary arteries (as confirmed by intravascular ultrasound) or resistive vessels.…”
Section: ␣-Adrenergic Coronary Constrictor Tone In Subjects With Normmentioning
confidence: 99%
“…Nevertheless, a 1 -adrenergic stimulation with methoxamine did not induce any effect on epicardial coronary cross-sectional area, nor on coronary blood flow. 6 Of note, intracoronary infusion of yohimbine, a selective a 2 -adrenergic blocker, did not change coronary diameter or coronary blood flow velocity, 22 while the stimulation with BHT-933, a selective a 2 -adrenergic receptor agonist, mediates microvascular constriction. 6 …”
Section: Alpha-adrenergic Receptors In the Normal Coronary Circulationmentioning
confidence: 95%
“…In human atherosclerotic coronary arteries, Indolfi et al 22 found that the a 2 -adrenergic receptor antagonist yohimbine induced a vasocontriction. This was interpreted as the result of the inhibition of presynaptic noradrenaline re-uptake and subsequent a 1 -adrenergic vasoconstriction.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…15 Sympathetic-mediated peripheral vasoconstriction is due to stimulation of post-synaptic α1-and α2-adrenoceptors in normal subjects as well as in heart failure, 16, 17 and sympathetic vasoconstriction has been documented in coronary circulation. 18 Therapeutic renal denervation has been explored in preclinical models 19 and in humans 20 since the 1950 s, when surgical renal denervation was shown to be a highly effective treatment for resistant hypertension in the clinical setting.…”
mentioning
confidence: 99%